Quantum efficiency of Pd/TiO 2 catalyst for photocatalytic reforming of methanol in ultra violet region - Bahruji, Hasliza; Maarof, Hasmerya; Abdul Rahman, Norizah (Springer Verlag, 2019)
The efficiency of Pd/TiO2 catalyst for photocatalytic reforming of methanol was investigated in ultra violet, UV region by monitoring the volume of H2 production and the number of incident photon using chemical actinometry method. 2-nitrobenzaldehyde solution was used to evaluate the number of incident photon from solar light by monitoring the rate of photochemical isomerisation to 2-nitrobenzoic acid. The activity of Pd/TiO2 catalyst varies across UV region with the ability to utilise the incident photon for H2 gas production is higher in UV-B. The quantum efficiency of the reaction was affected by the amount of catalysts concentration and the number of incident photons.